EXPLORING FIXED DOSE MEDICATION REGIMEN PRESCRIBING PATTERNS ACROSS CLINICAL SPECIALITIES - ANJALI J PATADIYA; DHARMIK M MEHTA (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: This study was to evaluate the medication regimen as a fundamental cornerstone of pharmacological therapy, focusing on the interplay between drug names, dosages, and schedules. Specifically, the study aimed to: Address the critical global challenge of non-adherence and its impact on disease progression and healthcare costs, Investigate how physicians across seven clinical specialties balance the pharmacological requirements of maintaining a steady-state with the practical, real-world challenges of patient adherence, Analyze the decision-making process behind prescribing patterns to identify strategies for optimizing therapeutic efficacy. Background: A medication regimen is the fundamental cornerstone of pharmacological therapy, defined by drug names, dosages, and schedules. While meticulous design is essential for therapeutic efficacy, non-adherence remains a critical global challenge, leading to disease progression and increased healthcare costs. This study explores how physicians across seven clinical specialties balance pharmacological steady-state requirements with the practical challenges of patient adherence. Methods: A structured, multi-specialty survey was conducted using a self-administered questionnaire. A target sample of 320 physicians was determined based on a 5% margin of error and 95% confidence level, with 250 responses achieved (78% response rate). The questionnaire underwent content validation by expert pharmacists and reliability testing (Cronbach’s alpha=0.78). Data analysis was performed using Microsoft Excel and inferential statistics, specifically Pearson’s Chi-square test, to determine the significance of observed differences across demographics and specialties. Results: Analysis of 250 physician responses (Mean distribution: 35.71, standard deviation [SD]: ±11.34) revealed that the thrice daily (TID) regimen is the most prevalent prescribing frequency (44%; SD: ±14.2%) to maintain therapeutic steady-state levels through meal-linked intervals. Statistically significant variation was observed across clinical specialties (p<0.001); psychiatry (50%) and pediatrics (45%) prioritized once daily (OD) dosing, whereas endocrinology (60%) and cardiology (55%) favored TID schedules. Demographic adaptations were highly evident, with over 75% of physicians transitioning to “minimum event” (OD/BID) schedules for pediatric and geriatric populations to reduce pill burden (p<0.001). While gender did not significantly dictate core dosing frequency (p>0.05), it significantly influenced drug selection and specific instructions related to pregnancy and breastfeeding. Conclusion: While the 3-times-a-day, meal-based regimen remains the clinical standard, physicians actively and significantly simplify schedules for pediatric and geriatric patients. The findings suggest that integrating meal-based reminders and “minimum event” logic into prescribing systems could enhance patient adherence and health outcomes.